Enterobacteria in the 21st century: a review focused on taxonomic changes - Soraya Morales-López; Jayr A Yepes; Juan C Prada-Herrera; Augusto Torres-Jiménez (Journal of Infection in Developing Countries)
Introduction: Enterobacteria are the main group causing infections in humans. The aim of this review is to present the new genera and the taxonomic changes that the Enterobacteriacea family has experienced in recent years.